OPTIMALISASI PERLINDUNGAN HUKUM BAGI PPPK YANG TERKENA PHK KETIKA MASIH DALAM PERIODE KONTRAK - Anggi Ardhanariswari; Hudha Bagus Setyadi (Universitas Stikubank, 2023)
The updated category in the ASN Law, namely Government Employees with Work Agreements, is a matter of controversy, especially on the issue of Termination of Employment (PHK). Which in this case raises aspects that are confronted starting from the professionalism of work to how the legal protection covers it. In this article, we will discuss the position of government employees with work agreements, what kind of legal protection covers PPPK in the event of termination of employment, and what legal steps can be taken to object to layoffs. In accordance with the description of the background and discussion, it can be concluded that the position of the PPPK as an employee of the State Civil Apparatus who is appointed as a Personnel Supervisor Officer according to the needs of government agencies who also have almost the same rights as civil servants. However, PPPK's legal protection is still in the development stage, so there is a need for further improvement and development to increase legal protection for PPPK and ensure that their rights are optimally protected. This is in line with PPPK's status which is still contractual so that its rights are not as strong as those of permanent civil servants. Therefore, efforts are needed to strengthen legal protection for PPPK in order to improve the welfare and work stability of PPPK and improve the quality of public services. One effort that can be done is to provide clearer job security guarantees for PPPK, as well as provide equal legal protection to permanent civil servants. With legal certainty that guarantees and optimizes this, of course this is also in line with good governance.